On the breeding season of Lipophrys pholis (Pisces: Blenniidae) at Arrábida, Portugal - Barata, Eduardo N. (2008)
Direct observations of egg masses on the shore indicates that Lipophrys pholis is a winter and spring spawner in Portuguese waters. The results are compared with those published for the British isles.